Power profile of top 5 results in world tour cycling races - van Erp, T.; Lamberts, R. P.; Sanders, D. (International Journal of Sports Physiology and Performance, 2022)
Purpose: This study evaluated the power profile of a top 5 result achieved in World Tour cycling races of varying types, namely: flat sprint finish, semi-mountain race with a sprint finish, semi-mountain race with uphill finish, and mountain races (MT).